Swayambhu Buddhacharya's relationship with Bungadya: - Bajracharya, Bajramuni (Cognition, 2022)
Swayambhu is located in ward 15 of Kathmandu Municipality and Bungamati is situated in ward 22 of Lalitpur Municipality. Bungadya: is the common deity of Nepalmandal whose image is kept six months in Bungamati and six months at Tahbahal of Lalitpur. Its chariot festival starts in the month of Baisakha. The main aim of the study is to explore Swayambhu Buddhacharya's relation with Bungam Lokesvara. What and how cultural activities are performed during the chariot festival by Budhacharyas. I spent 15 days in Swayambhu for data collection in 2016 Baisakha month. I selected some renowned priests of Swayambhu. I have applied the ethnographic method. During the course of data collection, I have interviewed with priests and observed animal sacrifice four days before starting the festival and involved in the preliminary procession of worship to Bungadya: at Pulchok. Books and articles have been used for description. This study is mostly completed based on the field research. Buddhacharya collects Pooja goods (objects) from each houses of Swayambhu then go to Hanuman Dhoka. The representative Buddhacharya first of all worship to Bungadya: in Pulchok before pulling chariot. Then, other devotees worship Bungadya:. On the way of returning home they deliver Prasad to the certain people. Instead of that, Prasad receiver gives Dakshina. Buddhacharya celebrate Jhwaglapagla Bhoy in Swayambhu. Four days before Panju sacrifice animal at Vayupur in Swayambhu at night and take away Swayambhu as Asana (seat) of Bungadya:. They have strong relation with Bungadya and Pānju of Bungamati. They do not keep marital relation with Bunga as well as Bunga do not marry with Swayambhu.